Method for improving high-temperature ductility of copper foil by regulating and controlling molecular weight of additive and application

During the processing of electrolytic copper foil, activated carbon is used to adsorb macromolecular additives in the diatomite filter, leaving small molecular weight additives to improve the high-temperature elongation and bending resistance of the copper foil, thus solving the problem of copper foil elongation in the existing technology. The problem of insufficient efficiency and bending resistance.

CN119332313APending Publication Date: 2025-01-21HUBEI NORD COPPER FOIL NEW MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411607846.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing methods cannot achieve coarse grains by screening the molecular weight of the additive, resulting in insufficient high-temperature elongation and bending resistance of lithium-battery copper foil.

Method used

By using activated carbon in a diatomaceous earth filter to adsorb macromolecular additives in the electrolyte, leaving behind small molecular weight additives, the latter can inhibit the deposition of copper foil and hide in grain boundaries, reducing the impact on grain boundary slip and high temperature migration. influence, thus improving the high-temperature elongation and bending resistance of copper foil.

Benefits of technology

Significantly improves the high-temperature elongation and bending resistance of copper foil, enhances the fracture resistance of lithium battery copper foil and the bending resistance of FPCB copper foil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332313A_ABST
    Figure CN119332313A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrolytic copper foil processing, and provides a method for improving the high-temperature elongation of a copper foil by regulating and controlling the molecular weight of an additive and application, and the method for preparing the copper foil and improving the derivation rate comprises the following steps: S1, preparing an electrolyte; s2, preparing a raw foil through electrolysis; the electrolytic raw foil temperature is 52 DEG C; the current is 30000 A when the raw foil is electrolyzed; s3, treating the surface of the raw foil; and S4, rolling and slitting to obtain finished foil. The invention discloses a technology for regulating and controlling the molecular weight of an additive, the technology for regulating and controlling the molecular weight of the additive is an important technical means in the production process of an electrolytic copper foil, and the microstructure and physical properties of the copper foil, including elongation and bending resistance, can be improved by influencing the reduction process of copper ions in an electrolyte. The electrolytic copper foil produced by the technical scheme has relatively high high-temperature elongation and bending resistance, can be used for preparing a lithium battery negative electrode material and an electronic circuit copper foil of an FCCL, and can bring a better use effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrolytic copper foil processing, and in particular to a method and application of improving the high-temperature elongation of copper foil by regulating the molecular weight of an additive. Background Art

[0002] Whether the electrolytic copper foil is used as the negative electrode material of lithium batteries or as the carrier of PCB, the elongation of the electrolytic copper foil is a measure of its ability to stretch without breaking under tensile force. For applications such as lithium-ion batteries and printed circuit boards, the elongation is an important physical performance indicator; copper foil with high elongation can better withstand various stresses during mechanical processing and use during battery manufacturing, thereby improving the safety and reliability of the battery.

[0003] The elongation of electrolytic copper foil has the following specific effects on battery performance: Impact on battery safety: Copper foil with high elongation can better withstand volume changes during battery charging and discharging, reduce the risk of breakage, and thus improve battery safety; during multiple charge and discharge processes, battery cells will experience expansion and contraction. If the elongation of the copper foil is insufficient, it may cause the current collector to break, thus affecting the overall performance and life of the battery.

[0004] Influence on battery cycle performance: Copper foil with high elongation can reduce deformation during battery cycling, thereby reducing poor contact between active materials and current collectors, maintaining battery performance and extending battery life.

[0005] Impact on production efficiency: In the battery manufacturing process, copper foil with high elongation can reduce the phenomenon of tape breakage in coating, rolling and other processes, and improve production efficiency.

[0006] Influence on electrode thickness: Copper foil with high elongation can withstand higher compaction force, which helps to increase the compaction density of battery electrodes, thereby reducing the thickness of the electrode sheets and further reducing the weight of the battery.

[0007] Influence on energy loss: Copper foil is the negative electrode current collector, and its main function is to conduct electricity; copper foil with high elongation helps reduce energy loss inside the battery and improve the overall conductivity of the battery.

[0008] Influence on power characteristics: Studies have shown that the thickness and elongation of copper foil will affect the power characteristics of the battery; copper foil with high elongation can help the battery provide higher power output.

[0009] Impact on battery life: Battery performance decays with increasing usage time, mainly manifested in decreased capacity and increased internal resistance. High elongation copper foil can slow down this decay process to a certain extent and extend the battery life.

[0010] However, the above existing methods for improving the high-temperature elongation of copper foil cannot achieve grain coarsening by screening the molecular weight of additives, and the lithium battery copper foil has poor fracture resistance and the FPCB copper foil has poor bending resistance. Therefore, we propose a method and application for improving the high-temperature elongation of copper foil by regulating the molecular weight of additives. Summary of the invention

[0011] The main purpose of the present invention is to absorb the macromolecular part of the additive through the activated carbon in the diatomaceous earth filter. Generally, macromolecules with a molecular weight > 450 can be adsorbed, while leaving the small molecular part of the additive. The small molecular weight additive still retains the original performance and inhibits the deposition of copper foil. It not only solves the problem of the copper layer being not dense without additives during the electrodeposition process, but also the small molecular structure of the additive is hidden in the grain boundary, which can less affect the grain boundary sliding and migration after high temperature, so it can show excellent high temperature elongation and bending resistance.

[0012] The technical solution of the present invention is as follows: A method for improving the high temperature elongation of copper foil by regulating the molecular weight of an additive, and a method for preparing copper foil to improve the derivatization rate, comprising the following steps: S1. Preparation of electrolyte; The copper metal is added into a copper dissolving tank containing sulfuric acid, and high-temperature air is blown in to dissolve the copper to prepare a main electrolyte. The main electrolyte is mixed with an additive solution through a diatomaceous earth filter, and then filtered through primary, secondary, and tertiary filters to obtain an electrolyte. The electrolyte is heat exchanged in a heat exchanger and then pumped into an electrolytic cell. S2, preparing raw foil by electrolysis; The temperature of electrolytic foil is 52℃.

[0013] The current during electrolytic foil production is 30,000A.

[0014] S3, surface treatment of raw foil; The outer surface of the raw foil is cleaned by a cleaning device, and the raw foil is dried after cleaning.

[0015] S4, rolling and slitting into finished foil; The dried raw foil is rolled up by a winding device and then cut into standard sizes to form finished foil.

[0016] The additive is added from the dirty liquid tank, and then passes through a diatomaceous earth filter. The diatomaceous earth filter filters out the macromolecular part of the additive, leaving the small molecular weight additive that can improve the elongation.

[0017] As a further technical solution of the present invention, the electrolyte in step S1 includes copper ions, sulfuric acid, chloride ions and mixed additives, and the mixed additives include agent A and agent B.

[0018] As a further technical solution of the present invention, the agent A in step S1 is a leveling agent in a large molecular weight range, and the agent B is a brightening agent.

[0019] As a further technical solution of the present invention, the additive in step S1 is added to the waste liquid tank in the copper dissolving system.

[0020] As a further technical solution of the present invention, a diatomaceous earth filter, a primary filter, a secondary filter and a tertiary filter are connected to the dirty liquid tank through a pipeline, wherein the primary filter is a bag filter, the secondary filter is a core filter, and the tertiary filter is an ultra-fine filter. The filtration accuracy of the primary filter is 1.5um, the filtration accuracy of the secondary filter is 1um, and the filtration accuracy of the tertiary filter is 0.5um.

[0021] As a further technical solution of the present invention, the diatomaceous earth filter contains coarse diatomaceous earth and fine diatomaceous earth, wherein the coarse diatomaceous earth is 100 mesh and the fine diatomaceous earth is a mixture of 300 mesh + 500 mesh.

[0022] As a further technical solution of the present invention, after the leveling agent with a large molecular weight range such as collagen in step S1 passes through the diatomaceous earth filter, the activated carbon adsorbs the large molecules, while the small molecule additives below 450 cannot be adsorbed, and continue to pass through the first, second, and third stage filtration, and flow into the foil raw machine to participate in the electrolytic copper deposition reaction. The small molecular weight additives are easily hidden in the grain boundaries and have a weak effect on the grain boundary sliding during the grain movement. The copper foil finally obtained has excellent high temperature elongation and bending resistance. The high temperature air blown in refers to a temperature between 50°C and 75°C.

[0023] As a further technical solution of the present invention, the copper ion concentration in the electrolyte in step S1 is 90g / L; the sulfuric acid content is 80g / L; the additives are composed of agent A, agent B, and chloride ions; wherein agent A is a leveling agent and agent B is a brightener; wherein agent A is added to a high-level tank; the agent B content is 5ppm and is added to a high-level tank; the chloride ion concentration is 30mg / L and is added to a waste liquid tank; the cathode in the electrolytic cell is a seamless drum-type titanium roller, and the anode of the electrolytic cell is a dimensionally stable tantalum-iridium-titanium anode plate.

[0024] As a further technical solution of the present invention, in step S1, agent A is one of collagen, gelatin, and HEC, and its content is 10ppm-50ppm; agent B is a brightening agent, and its content is 1ppm-5ppm.

[0025] An application of a finished product for improving the high-temperature elongation of copper foil by regulating the molecular weight of an additive. The finished copper foil product is prepared by the method for improving the high-temperature elongation of copper foil by regulating the molecular weight of an additive, and is used in the processing of electrolytic copper foil.

[0026] The working principle and beneficial effects of the present invention are: 1. In the present invention, by improving the elongation of the electrolytic copper foil, the overall performance of the battery can be significantly improved, meeting the demand for high-performance batteries in the fields of new energy vehicles, 3C digital products, etc.; 2. The method for improving the elongation of electrolytic copper foil in the present invention includes optimizing the electrolytic process, controlling the roughness of the smooth surface, using additives, heat treatment, etc.; 3. The additive control in the present invention is the most common method currently adopted by various enterprises, but general additives play the role of grain refinement, but grain refinement can significantly increase the tensile strength and reduce the elongation, so the general mechanism of action cannot play the role of significantly improving the elongation, while the present invention can significantly improve the elongation of copper foil; 4. The present invention achieves grain coarsening by screening the molecular weight of additives, which not only improves the fracture resistance of lithium battery copper foil, but also improves the bending resistance of FPCB (flexible circuit board) copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0028] Figure 1 The metallographic diagrams of the cross sections of the samples of Examples 1-2 and Comparative Example 1 of the present invention; Figure 2 For the present invention Figure 1 Color pictures; Figure 3 This is a schematic diagram of the location for adding additives of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1 The present invention provides a method for improving the high temperature elongation of copper foil by regulating the molecular weight of an additive, and the specific contents are as follows: S1: Electrolyte preparation Add copper metal to a copper dissolving tank containing sulfuric acid, blow in high-temperature air, dissolve copper to prepare the main electrolyte, mix the main electrolyte with the additive solution through a diatomite filter, and then filter through primary, secondary, and tertiary filters to obtain the electrolyte; the electrolyte is pumped into the electrolytic cell after heat exchange in a heat exchanger; the copper ion concentration in the electrolyte is 90g / L; the sulfuric acid content is 80g / L; the additives are composed of agent A, agent B, and chloride ions; agent A is a leveling agent, and agent B is a brightener. Agent A is collagen, and its content is 30ppm, which is added to the high-level tank (see Figure 2 ); Agent B is DPS, its content is 5ppm, added to the high-level tank. The chloride ion concentration is 30mg / L, added to the waste liquid tank; the cathode in the electrolytic cell is a seamless drum-type titanium roller, and the anode of the electrolytic cell is a dimensionally stable tantalum-iridium-titanium anode plate; S2, electrolysis to prepare raw foil; the temperature of electrolytic raw foil is: 52°C. The current size during electrolysis of raw foil is 30000A. S3, raw foil surface treatment; S4, winding and slitting into finished foil; Example 2 The difference between this embodiment and embodiment 1 is that agent A is added to the waste liquid tank during the preparation of the electrolyte, and the other aspects are the same.

[0031] Comparative Example 1 The difference between this comparative example and Example 1 is that no agent A and agent B are added during the preparation of the electrolyte, and the other aspects are the same.

[0032] experiment The relevant equipment and test methods are as follows: Metallographic analysis: Using the 3D ultra-depth microscope VHX-X1F provided by Keyence; Tensile strength and elongation test: According to the test method GB / T29847-2013, the tensile strength and elongation of the copper foil were tested at room temperature (about 25°C) using an AGS-X series universal material testing machine manufactured by SHIMADZU.

[0033] Bending test: FPC bending test machine provided by Dongling Electronics.

[0034] The basic physical properties test results of the electrolytic copper foils prepared in Examples 1-2 and Comparative Example 1 are shown in Table 1: Table 1 Physical properties and microscopic crystal test results of electrolytic copper foil Table 1 shows the physical properties of the electrolytic copper foil prepared according to the technical process provided by the present invention. After adding the additive A with molecular weight screening in Example 2, the high temperature elongation performance of the material is significantly improved (compared with Example 1 and Comparative Example 1). In addition, it is worth mentioning that the high temperature elongation and bending resistance of Comparative Example 1 are extremely low without adding any additives, which can be explained by the following Figure 1Explain, from Figure 1 It can be seen that there are obvious gaps between the grains of Control Example 1, so the copper foil is not densely grown, and thus cannot exhibit good physical properties. At the same time, compared with Example 1, Example 2 has large grains and is a block crystal that is easy to slip and grow and migrate, while Example 1 is a columnar crystal of different sizes, so it cannot show excellent elongation and bending resistance.

[0035] It should be noted that the present invention can significantly improve the overall performance of the battery by improving the elongation of the electrolytic copper foil, and meet the needs of new energy vehicles, 3C digital products and other fields for high-performance batteries. Methods for improving the elongation of electrolytic copper foil include optimizing the electrolysis process, controlling the roughness of the smooth surface, using additives, heat treatment, etc. Among them, additive regulation is the most common method currently adopted by various companies, but general additives have the effect of refining the grains. We all know that grain refinement can significantly increase the tensile strength and reduce the elongation, so the general mechanism of action cannot play a role in significantly improving the elongation. This paper achieves coarsening of the grains by screening the molecular weight of the additive, which not only improves the ability of lithium battery copper foil to resist fracture, but also improves the ability of FPCB (flexible circuit board) copper foil to resist bending.

[0036] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for improving the high temperature elongation of copper foil by regulating the molecular weight of an additive, characterized in that: The method for preparing copper foil to improve the derivatization rate comprises the following steps: S1. Preparation of electrolyte; The copper metal is added into a copper dissolving tank containing sulfuric acid, and high-temperature air is blown in to dissolve the copper to prepare a main electrolyte. The main electrolyte is mixed with an additive solution through a diatomaceous earth filter, and then filtered through primary, secondary, and tertiary filters to obtain an electrolyte. The electrolyte is heat exchanged in a heat exchanger and then pumped into an electrolytic cell. S2, preparing raw foil by electrolysis; The temperature of electrolytic foil is: 52℃; The current during electrolytic foil production is 30000A; S3, surface treatment of raw foil; The outer surface of the raw foil is cleaned by a cleaning device, and the raw foil is dried after the cleaning is completed; S4, rolling and slitting into finished foil; The dried raw foil is rolled up by a winding device, and after rolling up, it is cut into standard sizes to form finished foil; The additive is added from the dirty liquid tank, and then passes through a diatomaceous earth filter. The diatomaceous earth filter filters out the macromolecular part of the additive, leaving the small molecular weight additive that can improve the elongation.

2. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 1, characterized in that: In step S1, the electrolyte includes copper ions, sulfuric acid, chloride ions and mixed additives, and the mixed additives include agent A and agent B.

3. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 2, characterized in that: In step S1, the agent A is a leveling agent in a large molecular weight range, and the agent B is a brightening agent.

4. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 2, characterized in that: The additive in step S1 is added to the waste liquid tank in the copper dissolving system.

5. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 4, characterized in that: The dirty liquid tank is connected to a diatomaceous earth filter, a primary filter, a secondary filter and a tertiary filter through a pipeline, wherein the primary filter is a bag filter, the secondary filter is a core filter, and the tertiary filter is an ultra-fine filter. The filtering accuracy of the primary filter is 1.5um, the filtering accuracy of the secondary filter is 1um, and the filtering accuracy of the tertiary filter is 0.5um.

6. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 2, characterized in that: The diatomaceous earth filter contains coarse diatomaceous earth and fine diatomaceous earth, wherein the coarse diatomaceous earth is 100 meshes and the fine diatomaceous earth is a mixture of 300 meshes and 500 meshes.

7. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 2, characterized in that: In step S1, after the leveling agent with a large molecular weight range such as collagen passes through the diatomaceous earth filter, the activated carbon adsorbs the large molecules, while the small molecular weight additives below 450 cannot be adsorbed, and continue to pass through the first, second, and third stage filtration, and flow into the foil raw machine to participate in the electrolytic copper deposition reaction. The small molecular weight additives are easily hidden at the grain boundaries and have a weak effect on the grain boundary sliding during the grain movement. The copper foil finally obtained has excellent high temperature elongation and bending resistance.

8. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 2, characterized in that: In step S1, the copper ion concentration in the electrolyte is 90g / L; the sulfuric acid content is 80g / L; the additives are composed of agent A, agent B, and chloride ions; wherein agent A is a leveling agent and agent B is a brightener; wherein agent A is added to a high-level tank; the agent B content is 5ppm and is added to a high-level tank; the chloride ion concentration is 30mg / L and is added to a waste liquid tank; the cathode in the electrolytic cell is a seamless drum-type titanium roller, the anode of the electrolytic cell is a dimensionally stable tantalum-iridium-titanium anode plate, and the high-temperature air blown in has a temperature between 50°C and 75°C.

9. The method for improving the high temperature elongation of copper foil by regulating the molecular weight of additives according to claim 3, characterized in that: In step S1, agent A is one of collagen, gelatin, and HEC, and its content is 10ppm-50ppm; agent B is a brightener, and its content is 1ppm-5ppm.

10. An application of a finished product for improving the high temperature elongation of copper foil by regulating the molecular weight of an additive, characterized in that: The finished copper foil product is prepared by the method for improving the high-temperature elongation of the copper foil by regulating the molecular weight of the additive as described in any one of claims 1 to 9, and is used in the processing of electrolytic copper foil.